Design Of Temperature System On The Electrical Tank Heater Using PLC - Dewi, Astrie Kusuma; Sugirto, Ihrom; Hamdani, Chalidia Nurin; Septiani, Natasya Aisah (Jurnal Polimesin, 2024)
A temperature control system is required in any situationthat requires a certain temperature to remain stable.Likewise, in the electrical processtank heater that requires a control system, because the temperature is notby the set value will cause overheating it,causing the product temperature is not as desired and can even causea dangerous explosion. In this project, the design is carried outtemperature control on the prototype electrical tank heater usingPLC Nano V5.2 as the controller, and the control method used is fuzzy Sugeno.Fuzzy logic has a value of obscurity and obscuritybetween right and wrong and control systems. Membership value may varyfrom 0 to 1. This means a situation can have two values, “yes or no” and "right or wrong", so it seems as if there is a "gray" area. Fuzzy Sugenois a fuzzy inference method for the conditions represented inthe form of IF–THEN, where the system output is not a fuzzy set but a constant form. Test results on the prototype confirm that the systemcontrol with PLC as controller and fuzzy as control methodhas a good ability to adapt the time needed totake longer to reach a stable state at higher temperatures (33.5°C to 37°C).Then at lower temperatures (29°C to 33.5°C). Haiwell-capable interfaceschange set values, display real-time graphs, and send commands toset PWM.